Mortgage-backed securities - Andreas Fuster; David O. Lucca; James Vickery (Federal Reserve Bank of New York, 2022)
This paper reviews the mortgage-backed securities (MBS) market, with a particular emphasis on agency residential MBS in the United States. We discuss the institutional environment, security design, MBS risks and asset pricing, and the economic effects of mortgage securitization. We also assemble descriptive statistics about market size, growth, security characteristics, prepayment, and trading activity. Throughout, we highlight insights from the expanding body of academic research on the MBS market and mortgage securitization.
Keywords: G10; G12; G21; 330; mortgage finance; securitization; agency mortgage-backed securities; TBA; option-adjusted spreads; covered bonds